From COVID-19 to Resilience: Quantitative Methods in Economics and Business - Lina Novickytė; Jolanta Droždz; Radosław Pastusiak; Michał Soliwoda (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains 11 articles accepted for publication and published in the Special Issue From COVID-19 to Resilience: Quantitative Methods in Economics and Business of the MDPI Mathematics journal. These articles cover a wide range of topics analyzing economics and business situations during and post the COVID-19 pandemic. It is hoped that these selected research papers will be found to be impactful by the international scientific community and that these papers will facilitate further research on quantitative techniques for solving complex problems in various disciplines and application fields.
Keywords: 330; COVID-19; tourism industry; hospitality sector; interval-valued intuitionistic fuzzy set; k-means clustering; system structural harmonicity; synergetics; orderliness; entropy; generalized golden ratio (GGR); quantitative assessment; road safety; COVID-19 epidemic; Russia; Anscombe's quartet; Cook's distance; default rate; expected credit loss; gross domestic product; commodities; structure of copper futures prices; cointegration; contango; backwardation; extreme event contexts; entrepreneurial resilience; creative performance; institutional orientation; SEM; telecommunications; broadband; digitization; resilience; pandemics; business performance; financial analysis; COVID-19 pandemic; construction sector; Slovak enterprises; rural hospitality and tourism; agritourism; micro-businesses; agritourism performance; support for agritourism development; personal resident benefit; resident–micro-business interaction; COVID-19 news; volatility; granger causality; time-varying; time series; financial markets; MSGARCH; symmetry; regime changes; safe haven; hedge properties; Bitcoin; gold; government bond price volatility; government policy responses; international financial markets; containment and closure; economic support; panel quantile regression